THE EFFECT OF FERMENTED BRAN TIME ON IMPROVING WATER QUALITY AND GROWTH OF VANNAME SHRIMP (Litopenaeus vannamei) - Febri, Suri Purnama; Syafi`i, Adnan; Haser, Teuku Fadlon; Khairi, Ikhsanul (Universitas Mataram, 2025)
Vanname shrimp is one of the commodity products that have high economic value in Indonesia and abroad. This study aims to determine the right time to give rice bran fermentation in improving the quality and growth of vannamei shrimp. The study used an experimental method with 4 treatments that were repeated as many as 3 replicates. The treatments tested were P1 giving bran fermentation on day 0 before stocking, P2 giving bran fermentation on day 10 after stocking, P3 giving bran fermentation on day 20 after stocking, and P4 giving bran fermentation on day 30 after stocking. The results of the treatment showed a significant effect on absolute length growth, absolute weight growth, and daily growth rate. Meanwhile, survival and feed conversion ratio did not have significant differences, as well as water quality. In general, water quality was not affected by the treatments given. The highest absolute length growth was produced in the P3 of 4.1 ± 0.01cm, while the lowest absolute length growth was obtained in the P1 with a result of 3.6 ± 0.0. The highest absolute weight growth was obtained in the P3 with the results of 2.61 ± 0.01gr, while the lowest absolute weight growth was produced in the P1 of 2.13 ± 0.03gr. Similarly, the highest daily growth rate was produced in the P3 with the results of 3.6 ± 0.0. Keywords: Vanname shrimp, fermentation, rice bran, water quality, growth